Persecution and Toleration in Reformation Europe - Sutherland, Nicola M. (Studies in church history, 1984)
Persecution is self-explanatory, but toleration, when one starts to consider it, blurs like the recollection of a dream. To what, in the first place, does toleration refer: to deviant opinions, deviant practices, or to potentially subversive organisations? Genuine toleration has probably always been very rare—and probably still is. In the sense of complete religious liberty, it was not generally accepted until varying dates in the nineteenth century. Then it had more to do with materialism and indifference than with any generous spirit of tolerance. If, in the sixteenth century, toleration was not entirely unknown—both in theory and in practice—it must be attributed to something more compelling than ‘a disposition to be patient with the opinions of others’—in the OED’s rather engaging definition. For one thing, toleration was not then regarded as a particularly desirable virtue, and therefore not widely entertained as an ideal. The ideal was rather that God, in his mercy and wisdom, should reunite the Church, or churches. This was expressed, for example, in the preamble to the edict of Nantes in 1598, though one could discount it as propaganda.